2013
DOI: 10.1149/2.022304jes
|View full text |Cite
|
Sign up to set email alerts
|

How Do Reactions at the Anode/Electrolyte Interface Determine the Cathode Performance in Lithium-Ion Batteries?

Abstract: Today, it is common knowledge, that materials science in the field of electrochemical energy storage has to follow a system approach as the interactions between active materials, electrolyte, separator and various inactive materials (binder, current collector, conductive fillers, cell-housing, etc.) which are of similar or even higher importance than the properties and performance parameters of the individual materials only. In particular, for lithium-ion batteries, it is widely accepted that the electrolyte i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 56 publications
2
96
0
Order By: Relevance
“…An increase in upper cutoff potential of a LiCoO 2 electrode when cycled versus graphite was reported by Krueger et al in a reference electrode study. 33 Similarly, Beattie et al recently demonstrated the evolution to higher cycling potentials of both electrodes in a LiNi 0.8 Co 0.15 Al 0.05 O 2 /silicon couple. 34 State-of-the-art layered oxides are not cycled over their entire theoretical capacity span both in order to stay within the stability windows of the electrolyte and to avoid irreversible structural changes detrimental to their performance.…”
Section: Resultsmentioning
confidence: 83%
“…An increase in upper cutoff potential of a LiCoO 2 electrode when cycled versus graphite was reported by Krueger et al in a reference electrode study. 33 Similarly, Beattie et al recently demonstrated the evolution to higher cycling potentials of both electrodes in a LiNi 0.8 Co 0.15 Al 0.05 O 2 /silicon couple. 34 State-of-the-art layered oxides are not cycled over their entire theoretical capacity span both in order to stay within the stability windows of the electrolyte and to avoid irreversible structural changes detrimental to their performance.…”
Section: Resultsmentioning
confidence: 83%
“…Likely, because there are several problems to overcome before it is possible to incorporate this process into a commercial battery cell manufacturing process, for example the evaporation of the electrolyte solvents, the high reactivity of the Li metal foil or the problem of high surface area lithium (HSAL) formation. However, Kim et al also presented that the external shorting with Li metal enables a delicate control on the degree of pre-lithiation (Figure 4), which is of high importance, especially with a focus on anode/cathode capacity balancing [28,56], SEI formation and the prevention of lithium metal plating at the negative electrode [30]. They conceived a scalable roll-to-roll process based on external shorting with Li metal foil for the pre-lithiation of carbon-coated silicon monoxide (c-SiO x ; x ≈ 1).…”
Section: Concepts For Electrochemical Pre-lithiationmentioning
confidence: 99%
“…The rate of degradation depends on various storage and operating conditions such as voltage, current, temperature and pressure [6,12]. These can all lead to various degradation mechanisms in different parts of the cell such as solid electrolyte interphase (SEI) layer formation at the negative electrode or metal dissolution at the positive electrode.…”
Section: Introductionmentioning
confidence: 99%